METODE AL-QUR’AN DALAM MEMBANGUN JIWA KEBANGSAAN - Nopiansah, Maolana (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2023)
The society that has been formed is bound by ties of religion, ethnicity, race, a sense of interdependence, mutual influence on work effectiveness and efficiency, has the same characteristics, and laws that regulate these relationships. The more ties that bind, the stronger the bonds of a society. The crystallized national consciousness of the Indonesian nation was born from a sense of shared fate and shared responsibility. This sense of fate is a result of colonialism in the past. National awareness has succeeded in forming Indonesia's national outlook as stated in the Youth Pledge. The feeling of one homeland, one nation and one language is a strong bond and needs to be preserved. National awareness has given birth to a united determination, declared politically as an independent and sovereign nation in the Proclamation of 17 August 1945. A national state like Indonesia is a state formed on the basis of a national spirit. The aim is to build a shared future under one and the same country even though the people have different religions, races, ethnicities or groups. Plurality is a very valuable cultural treasure that can be used as social capital to build a peaceful national life, but on the other hand it is a very heavy social burden. The history of the Indonesian nation records a multidimensional crisis in 1997 which threatened the integrity of the Republic of Indonesia. The phenomenon of this crisis is a decline in national morals, such as a lack of politeness and honesty among the Indonesian people, and a decrease in their attention to applicable laws. The causes are factors originating from within the country such as weak understanding and practice of religion and factors originating from abroad such as the influence of globalization